Rational Design and Preparation of Functional Hydrogels for Skin Wound Healing - Hao, Ruinan; Cui, Zhuoyi; Zhang, Xindan; Tian, Ming; Zhang, Liqun; Rao, Feng; Xue, Jiajia (Frontiers in Chemistry, 2022)
Skin wound healing often contains a series of dynamic and complex physiological healing processes. It is a great clinical challenge to effectively treat the cutaneous wound and regenerate the damaged skin. Hydrogels have shown great promise for skin wound healing through the rational design and preparation to endow with specific functionalities. In the mini review, we firstly introduce the design and construction of various types of hydrogels based on their bonding chemistry during cross-linking. Then, we summarize the recent research progress on the functionalization of bioactive hydrogel dressings for skin wound healing, including anti-bacteria, anti-inflammatory, tissue proliferation and remodeling. In addition, we highlight the design strategies of responsive hydrogels to external physical stimuli. Ultimately, we provide perspectives on future directions and challenges of functional hydrogels for skin wound healing.